Internal and External Factors in the Development of the Bhakti Pamesun Village Cooperative in Jujuhan District of Bungo Regency, Indonesia - Pitriani Pitriani; Sahat Saris; Lili Suryani (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
The growth in the number of cooperatives in Indonesia has not always been accompanied by increased institutional sustainability, including in Jambi Province, where a high proportion of cooperatives remain inactive. Previous studies generally treat the determinants of village cooperative development separately (internal vs. external). They are normative, leaving limited empirical evidence on how working capital constraints and dependence on member savings interact with external opportunities, such as business partnerships and technology adoption, in long-established village cooperatives. This study aims to analyze the internal and external factors influencing the development of the Bhakti Pamesun Village Cooperative Unit (KUD) in Jujuhan District, Bungo Regency, and to identify their implications for the sustainability of cooperatives. The research uses a descriptive design with a survey approach, including observation, structured interviews, and questionnaires, administered to purposively selected administrators and active members. The analysis was conducted using simple qualitative and quantitative descriptive methods. The results show that the cooperative's internal strengths lie in its relatively large membership base, the stability of its basic and mandatory savings, and its orderly financial management practices. However, the cooperative faces structural weaknesses, including limited working capital and a high dependence on member savings. Externally, marketing partnerships with PT Incasi Raya Group and the use of agricultural technology (e.g., egrek and cutting machines) open up opportunities for operational efficiency and market access. However, fluctuations in palm oil prices and low adoption of advanced technology remain significant challenges. These findings emphasize the need for a development strategy that links human resource capacity building, diversification of capital sources beyond member savings, and expanded use of technology through continuous assistance. The limitations of this study include its focus on a single cooperative case and its descriptive design; therefore, further research using comparative studies or quantitative approaches is recommended to test the causal relationship between factors and cooperative performance. The growth in the number of cooperatives in Indonesia has not always been accompanied by increased institutional sustainability, including in Jambi Province, where a high proportion of cooperatives remain inactive. Previous studies generally treat the determinants of village cooperative development separately (internal vs. external). They are normative, leaving limited empirical evidence on how working capital constraints and dependence on member savings interact with external opportunities, such as business partnerships and technology adoption, in long-established village cooperatives. This study aims to analyze the internal and external factors influencing the development of the Bhakti Pamesun Village Cooperative Unit (KUD) in Jujuhan District, Bungo Regency, and to identify their implications for the sustainability of cooperatives. The research uses a descriptive design with a survey approach, including observation, structured interviews, and questionnaires, administered to purposively selected administrators and active members. The analysis was conducted using simple qualitative and quantitative descriptive methods. The results show that the cooperative's internal strengths lie in its relatively large membership base, the stability of its basic and mandatory savings, and its orderly financial management practices. However, the cooperative faces structural weaknesses, including limited working capital and a high dependence on member savings. Externally, marketing partnerships with PT Incasi Raya Group and the use of agricultural technology (e.g., egrek and cutting machines) open up opportunities for operational efficiency and market access. However, fluctuations in palm oil prices and low adoption of advanced technology remain significant challenges. These findings emphasize the need for a development strategy that links human resource capacity building, diversification of capital sources beyond member savings, and expanded use of technology through continuous assistance. The limitations of this study include its focus on a single cooperative case and its descriptive design; therefore, further research using comparative studies or quantitative approaches is recommended to test the causal relationship between factors and cooperative performance.